ChemInform Abstract: Palladium‐Catalyzed Regio‐ and Stereoselective Chlorothiolation of Terminal Alkynes with Sulfenyl Chlorides. Issue 25 (24th June 2014) - Iwasaki, Masayuki; Fujii, Tomoya; Yamamoto, Arisa; Nakajima, Kiyohiko; Nishihara, Yasushi
Abstract The reaction proceeds with complete (Z)‐selectivity.